2016
DOI: 10.5713/ajas.15.0396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Purple Rice (<i>Oryza sativa</i> L. Var. Glutinosa) on the Quality of Pork and Pork Products

Abstract: Purple rice is a strain of glutaneous rice rich in anthocyanins and γ-oryzanol. Both types of compounds are involved in antioxidant and lipid metabolism of mammals. Three experimental diet types were used which consisted approximately by half either of purple rice, white rice or corn. Diets were fed to 3×10 pigs growing from about 30 to 100 kg. Meat samples were investigated either as raw or cured loin chops or as smoked bacon produced from the belly. Various physicochemical traits were assessed and data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The effect of antioxidant supplementation in the diet was consistent with effects observed in previous studies [ 48 , 52 ], whereby black rice was fed to pigs and it was reported that TBARS content in raw meat reduced over time in storage. Chikwanha et al [ 56 ] reported a reduction in lipid and protein oxidation of raw meat when grape pomace was added to the diet of lambs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The effect of antioxidant supplementation in the diet was consistent with effects observed in previous studies [ 48 , 52 ], whereby black rice was fed to pigs and it was reported that TBARS content in raw meat reduced over time in storage. Chikwanha et al [ 56 ] reported a reduction in lipid and protein oxidation of raw meat when grape pomace was added to the diet of lambs.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the current results indicated that LD samples obtained from cattle fed higher amounts AER had lower values for a*, b*, chroma, and hue, and less intense and vivid color than the control samples at day 1 of storage. Similarly, Jaturasitha et al [ 48 ] reported that feeding purple rice to fatten pigs resulted in lower a* values compared with feeding them white rice. In addition, Jerónimo et al [ 49 ] reported that lamb fed 6% vegetable oil in diets had lower a* values due to high PUFA content in the meat, which was susceptible to high myoglobin oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Villasante et al [74] found an increase in the percentages of total n-3 PUFA in the plasma of rainbow trout-fed anthocyanins-rich purple corn extract. Jaturasitha et al [75] reported a high rate of n-3 PUFA in raw loin chops of pigs fed anthocyanins-rich purple rice extract, indicating bioactive compounds such as anthocyanins in ARRE may affect the meat content from n-3 and n-6 PUFA. Anthocyanins may encourage the conversion of α-linolenic acid to EPA and DHA [73].…”
Section: Chemical and Fatty Acid Composition Of The Breast Musclesmentioning
confidence: 99%
“… Jerónimo et al (2012) did not observe changes in any lamb meat color parameter when fed grape seed extract rich in anthocyanins. Inclusion of purple rice-rich anthocyanins in pork diets did not modify meat L*, a*, and b* ( Jaturasitha et al, 2016 ). In broiler diets, increasing grape pomace rich in anthocyanins linearly decreased redness and resulted in paler meat ( Kasapidou et al, 2016 ; Aditya et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%